2016
DOI: 10.1097/sap.0000000000000834
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Financial Conflicts of Interest in Plastic Surgery

Abstract: Self-reported COI are uncommon in plastic surgery research. Our results provide evidence that certain types of financial COI are more likely than others to be associated with the presentation of positive findings. This analysis suggests that certain investigators may be more biased, consciously or unconsciously, by the type of financial benefit offered by industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
10
0
3
Order By: Relevance
“…Conversely, chairs and chiefs had the lowest engagement among leadership holders. This may be due to limited time, competing interests, and the concern of the perception of bias that occurs when physicians accept industry contributions [3,31,32]. Our findings also suggest that women receive significantly smaller total sums for speaker sponsorship than their male peers.…”
Section: Plos Onementioning
confidence: 66%
“…Conversely, chairs and chiefs had the lowest engagement among leadership holders. This may be due to limited time, competing interests, and the concern of the perception of bias that occurs when physicians accept industry contributions [3,31,32]. Our findings also suggest that women receive significantly smaller total sums for speaker sponsorship than their male peers.…”
Section: Plos Onementioning
confidence: 66%
“…COI are associated with the publication of positive research findings, 6 , 23 , 24 including among plastic surgery investigators. 25 COI also potentially affect national specialty guidelines. A 2011 British Medical Journal article reported that a large percentage of guideline panelists have substantial financial relationships with industry.…”
Section: Discussionmentioning
confidence: 99%
“…Holding consultantship or employee positions had a statistically significant association with the publication of positive research findings ( P < 0.001). 25 These findings suggest that certain relationships with industry—in particular surgeons holding consultant or employee positions—may be most critical to report under the Sunshine Act. Moreover, it may suggest that journal editorial boards should focus their energy on defining and highlighting COI that are at higher risk for bias, and making these clear to the scientific readership.…”
Section: Discussionmentioning
confidence: 99%
“…Die Arbeit von Lopez et al zeigte, dass selbstberichtete Interessenkonflikte in der Forschung der Plastischen und Ästhetischen Chirurgie eher selten sind, indes bestehende Interessenkonflikte eher mit der Präsentation positiver Ergebnisse in Verbindung gebracht werden. Die Arbeit deutet darauf hin, dass bestimmte Forscher bewusst oder unbewusst, auch durch die Art des finanziellen Nutzens, stärker beeinflusst werden können 20 . Auch die Erkenntnisse von Probst et al zeigen, dass die Finanzierung von chirurgischen Studien durch die Industrie zu einer positiven Berichterstattung über die Forschungsergebnisse führt, sodass die Beteiligung der Industrie an der chirurgischen Forschung umso mehr auf vollständiger Transparenz beruhen muss, um wissenschaftliche Integrität und Unabhängigkeit gewährleisten zu können 21 .…”
Section: Diskussionunclassified
“…1). Von den genannten RCTs stammten die meisten aus den USA (124) gefolgt von Brasilien (27), China (21), England (20) und Kanada (18). Die Verteilung der Publikationsjahre porträtiert eine zunehmende Anzahl an ▶tab.…”
Section: Ergebnisseunclassified